Legal Analysis of Corporate Social Responsibility Fund Management by Financial Technology Companies in Indonesia - Muhammad Syahri Ramadhan; Yuli Prasetyo Adhi; Maria Prehatiningsih Utami; Taufik Purbo Satrio (Universitas Sriwijaya, 2026)
Mining and plantation sectors have frequently raised legal issues concerning the management of Corporate Social Responsibility (CSR) funds. The financial technology (fintech) sector, which merges financial services with digital technology, is likewise not exempt from CSR obligations. However, unlike traditional extractive industries whose environmental and social impacts are tangible and localized, fintech companies operate predominantly in the digital sphere, rendering their societal effects less direct and more difficult to measure. This condition necessitates a comprehensive legal study on the management of CSR funds within the fintech industry. Employing normative legal research with a prescriptive approach, this paper examines statutory provisions, doctrines, and regulatory frameworks relevant to CSR obligations in Indonesia. The analysis reveals that Indonesian law mandates CSR implementation even for companies whose business activities do not involve natural resource management, thereby allowing CSR programs to extend beyond the immediate corporate environment. Sociologically, this creates an opportunity for fintech companies to direct CSR initiatives toward digitalization programs addressing Indonesia's persistently low digital literacy. Nevertheless, existing regulations contain no fintech-specific provisions, generating ambiguity between mandatory obligation and voluntary practice. The government should therefore formulate a specialized regulatory framework requiring fintech companies to implement CSR programs aligned with national digital development needs, ensuring legal certainty and maximizing social impact.